Pengaruh Kecerdasan Interpersonal terhadap Profesionalisme Pengurus Organisasi Santri Putri Nurulhuda (Ostada) - Mila Chamilia; Fayruzah El-Faradis (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
This study aims to know the influence and how much the influence of interpersonal intelligence on manager professionalism (OSTADA) Pakandangan Sumenep. This research used quantitative approach. The population of this research is all managers of organization at female student Nurulhuda (OSTADA) Pakandangan Bluto Sumenep 33 person. While the data collection techniques used are questionnaire, observation and documentation. Data analysis techniques in this research is simple linear regression test with Statistical Package For Sosial Science (SPSS) For Windows version 24.0. The results showed that there are influences of interpersonal intelligence on manager professionalism organization Nurulhuda (OSTADA) Pakandangan Bluto Sumenep. This is evident first with the anova table value in the significance column listed as 0,000 under 0,05. Second by comparing the count F value with the F table value, where the F count is equal to 39.690 bigger than F table value with 2,50. The great influence of interpersonal intelligence on professionalism of the management at female organization Nurulhuda (OSTADA) Pakandangan Bluto Sumenep is equal to 0,561 which means 56,1%. This can be seen from the value of R Square in the Model Summary table in the column on Standard Error Of The Estimate, while the remaining 43,9% is influenced by several other factors